Effect of salinity on the denitrification of the sulfur-based autotrophic denitrification system - Zhaoliang Zhu; Hao Zhou; Jiale Zou; Jiaxiang Wang (Water Cycle, 2023)
This study investigated the effect of gradual salt concentration increases on the nitrogen removal performance from a sulfur-based autotrophic denitrification (SAD) process. A continuous operation reactor was used to study the adaptability of sulfur-based autotrophic denitrifying bacteria to changes in salinity. The study focused specifically on the effects of SO42− and Cl− on the activity of SAD bacteria. When the concentration of SO42− was 0∼4 ​g/L, NO3−-N was removed at more than 97%. When the concentration of SO42− increased to 15 ​g/L, the removal of NO3−-N decreased to 51%. When the concentration of NaCl was 0∼30 ​g/L, the removal rate of NO3−-N was all greater than 97%. When the concentration of NaCl increased to 80 ​g/L, the removal rate of NO3−-N decreased to 34.6%. When the NaCl concentration was 50 ​g/L, the removal rate of NO3−-N decreased to 80.59% at first, and the removal rate of NO3−-N recovered to 98% after 16 days of operation. When the NaCl concentration increased to 80 ​g/L, the NO3−-N removal rate decreased to 50%, and the reactor still could not recover its performance after long-term operation. The growth of halophilic heterotrophic bacteria with the increase of NaCl concentration leads to an increase in the abundance of Proteobacteria. The higher concentration of Cl− seriously inhibits the growth of Sulfurimonas and Thiobacillus, decreasing the effectiveness of bacteria to remove nitrogen.